Annual Clinicopathological Analysis of Ovarian Tumours at TUTH - Amatya, Sapana; Gurung, Geeta; Rana, Ashma (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v4i2.5041 NJOG 2010 Jan-Feb; 4(2): 18-24